2015
DOI: 10.1016/j.ejphar.2015.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Would calcium or potassium channels be responsible for cardiac arrest produced by adenosine and ATP in the right atria of Wistar rats?

Abstract: Autonomic nerves release ATP, which is processed into adenosine in the synaptic cleft. Adenosine and ATP exert a negative chronotropic effect in the heart. This study aims to evaluate adenosine and P2 receptors and cellular signalling in cardiac arrest produced by purines in the heart. Right atria of adult Wistar rats were used to evaluate the effects of adenosine, ATP and CPA (an adenosine A1 receptor agonist), in the presence and absence of DPCPX, an adenosine A1 receptor antagonist. Effects of adenosine A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Our theory that the negative chronotropic effect of ATP in spontaneously beating atria strips is mediated primarily via the activation of nucleotide-sensitive P2 purinoceptors is further supported by the fact that 1) it was reproduced by the enzymatically stable ATP analogue, ATPγS, 2) it was blocked by PPADS, a non-selective P2 purinoceptors antagonist exhibiting no affinity for adenosine receptors, and 3) prevention of ATP breakdown into adenosine with the NTPDase inhibitor, POM-1, increased rather than decreased ATP-induced negative chronotropism. Our findings agree with previous reports in the literature about the role of ATP and related adenine nucleotides on cardiac function (Versprille and van Duyn, 1966; Lundberg et al, 1984; Camara et al, 2015) and questions the most accepted hypothesis that the negative chronotropic action of ATP is most likely due to A 1 receptors activation after its rapid conversion into adenosine (Pelleg and Belhassen, 2010). While this hypothesis neglected the pivotal role of P2 purinoceptors in the control of spontaneous activity of the SAN, it has been demonstrated that ATP was more potent than adenosine in reducing heart rate (Pelleg et al, 1985; Sharma and Klein, 1988), which was interpreted as being due to an additional vagal reflex of ATP via sensory P2X2 and/or P2X3 receptors (Pelleg et al, 1987; Xu et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our theory that the negative chronotropic effect of ATP in spontaneously beating atria strips is mediated primarily via the activation of nucleotide-sensitive P2 purinoceptors is further supported by the fact that 1) it was reproduced by the enzymatically stable ATP analogue, ATPγS, 2) it was blocked by PPADS, a non-selective P2 purinoceptors antagonist exhibiting no affinity for adenosine receptors, and 3) prevention of ATP breakdown into adenosine with the NTPDase inhibitor, POM-1, increased rather than decreased ATP-induced negative chronotropism. Our findings agree with previous reports in the literature about the role of ATP and related adenine nucleotides on cardiac function (Versprille and van Duyn, 1966; Lundberg et al, 1984; Camara et al, 2015) and questions the most accepted hypothesis that the negative chronotropic action of ATP is most likely due to A 1 receptors activation after its rapid conversion into adenosine (Pelleg and Belhassen, 2010). While this hypothesis neglected the pivotal role of P2 purinoceptors in the control of spontaneous activity of the SAN, it has been demonstrated that ATP was more potent than adenosine in reducing heart rate (Pelleg et al, 1985; Sharma and Klein, 1988), which was interpreted as being due to an additional vagal reflex of ATP via sensory P2X2 and/or P2X3 receptors (Pelleg et al, 1987; Xu et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…However, one cannot exclude ATP conversion into adenosine during incubation with the nucleotide, yet even if this had occurred in our experimental conditions the amount of adenosine falls below the threshold to activate A 1 receptors in the SAN. These findings contrast with those obtained by Camara et al (2015); these authors concluded that the negative chronotropic effect of ATP was dependent on A 1 receptors activation by using DPCPX in a concentration (1 µM) that is more than 2,000-fold higher than the K i value for this antagonist to block the A 1 receptor (Camara et al, 2015). Under such conditions, off-target effects of DPCPX may appear, which include inhibition of phosphodiesterases that may explain reversal of the negative chronotropic effect of ATP (Camara et al, 2018).…”
Section: Discussioncontrasting
confidence: 59%
“…It has been proposed that this modulatory role of A1R on cardiac function finely adjusts cardiac chronotropism, and thus reduces the incidence of cardiac arrhythmias [ 5 , 17 , 49 ]. It has also been suggested that this cardioprotective action of ADO mediated by cardiac A1R could occur in different physiological and pathological conditions, including CIR and cardiac pre- and post-ischemic conditioning [ 17 , 18 , 50 , 51 ]. Interestingly, heparin and LMWHs can prevent cardiac arrhythmias associated with sudden death caused by ventricular tachycardia, torsades de pointes , and ventricular fibrillation, and first- and second-degree AVB in animal CIR models, as well as in isolated rat atria [ 17 , 18 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this strategy could be useful to prevent sudden death due to severe arrhythmias caused by cardiac collapse in patients with AMI. It is important to note that pharmacological activation of cardiac A1R reduces the excitability of cardiac cells [ 28 , 50 ], possibly reducing the probability of lethal atrioventricular blocks. In this study we demonstrate that, at least in part, the antiarrhythmic effect of ENOX is due to its action on the cAMP/ADO extracellular pathway in cardiac cells, preventing arrhythmias and death caused by cardiac collapse in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation